The correlation between miR-21 single nucleotide polymorphisms and the susceptibility of non-small cell lung cancer - Miao Zhang; Ming Zhang; Ruixue Han; Xin Yu; Zhaolu Song (Journal of Cardiothoracic Surgery)
Abstract Background There are still gaps in the study of the miRNA and its SNPs in some diseases such as non-small cell lung cancer (NSCLC). The study aimed to provide useful information on the treatment of NSCLC by investigating the association between miR-21 and its SNPs and NSCLC susceptibility. Methods The serum of NSCLC patients (n = 205) and cancer-free controls (n = 217) were collected in this study for RNA extraction. The qRT-PCR was used to evaluate the expression of miR-21 and Taqman qPCR was used for genotyping and quantifying miR-21 SNPs (rs1292037, rs6504593). The association of the expression of miR-21, the miR-21 SNPs and their interactions with the susceptibility of NSCLC patients were analysed using logistic regression analysis in this study. Results This study showed that the overexpression of miR-21 was related to NSCLC. The C allele and CC genotypes of rs1292037 and rs6504593 were associated with the increased risk of NSCLC susceptibility. Moreover, the interactions of rs1292037 and rs6504593 were also a risk factor for NSCLC. The CC genotypes of rs1292037 and rs6504593 were associated with the increase of miR-21 expression. Conclusion The overexpression of miR-21, the miR-21 SNPs rs1292037 and rs6504593 and their interactions were associated with NSCLC susceptibility. MiR-21 and its SNPs have potential for being targets in the therapy of NSCLC. This study provided important information for the treatment of NSCLC.